Concepções prévias de estudantes do ensino médio sobre solubilidade e o desenvolvimento de atividades experimentais como ferramenta para a melhoria do ensino - Azzolin, Kelli Anne Santos (2012)
The knowledge of previous conceptions of students is an important tool in the teaching-learning process, since it can significantly help the planning of educational activities. Solubility is a fundamental concept in Chemistry present in a wide range of everyday situations; however, it is little explored regarding previous conceptions. In this context, this study aimed to investigate the previous conceptions of high school students on solubility, to evaluate if Biology and Chemistry teachers develop experimental and interdisciplinary activities on the theme and to elaborate a booklet with experiments on solubility. The study was performed in public schools of Santa Maria-RS and Rosário do Sul-RS and involved 314 students and 30 teachers of Biology and Chemistry. In order to investigate the previous conceptions of students, we used a semi-structured questionnaire for data collection consisting of questions concerning the concept of solubility, the importance of this concept in everyday life and the existence of correlation of this content with the content studied in Biology. With regard to Biology and Chemistry teachers, we used a closed questionnaire with issues related to the workload of teachers, the realization of practical classes and the interdisciplinary approach of the solubility content. In general, we verified that students have knowledge about solubility, but little is based on scientific knowledge. Students also reported the importance of this knowledge mainly regarding the food. The results obtained also showed that most of the teachers do not work the theme solubility in an interdisciplinary way or perform experimental activities related to it. Therefore, we can conclude that some teachers still have a fragmented and compartmentalized teaching, where the student is a mere receiver of knowledge. After the analysis of the data obtained, a booklet will be prepared with experiments on solubility, which will be distributed to teachers participating the research in order to help them carry out these experiments and develop new experimental activities in the classroom.